The Performance of Private and Cooperative Socialist Organization: Postwar Yugoslav Agriculture - Boyd, Michael L. (The Review of Economics and Statistics, 1987)
Socialist enterprises in Yugoslav agriculture show higher levels of productivity than private producers. The author examines the sources of these differences with total factor productivity estimates based on sectoral aggregate Cobb-Douglas production functions which permit separation of environmental, policy, and organizational effects. The results support the following conclusions: cooperative socialist enterprises are not inherently inefficient and can even outperform private producers; both types of producers were responding to their environment and their differential rates of technological change reflect the different constraints they faced; and socialist enterprises exhibited technology adoption behavior similar to nonsocialist enterprises elsewhere. Copyright 1987 by MIT Press.